2016
DOI: 10.1186/s12864-016-2971-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of the conidiation pattern shift of the entomopathogenic fungus Metarhizium acridum in response to different nutrients

Abstract: BackgroundMost fungi, including entomopathogenic fungi, have two different conidiation patterns, normal and microcycle conidiation, under different culture conditions, eg, in media containing different nutrients. However, the mechanisms underlying the conidiation pattern shift are poorly understood.ResultsIn this study, Metarhizium acridum undergoing microcycle conidiation on sucrose yeast extract agar (SYA) medium shifted to normal conidiation when the medium was supplemented with sucrose, nitrate, or phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…Recently, studies about microcycle conidiation mostly focus on the phenotypic observation in different fungi (Souza-Paccola et al, 2015; van Heerden et al, 2016; Rosli et al, 2018). In the preliminary work in our lab, we found that normal conidiation and microcycle conidiation are involved in lipid metabolism, sugar chain biosynthesis, and metabolism and translation (Wang Z. et al, 2016). Nevertheless, the mechanism of the shifts of the two conidiation patterns remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies about microcycle conidiation mostly focus on the phenotypic observation in different fungi (Souza-Paccola et al, 2015; van Heerden et al, 2016; Rosli et al, 2018). In the preliminary work in our lab, we found that normal conidiation and microcycle conidiation are involved in lipid metabolism, sugar chain biosynthesis, and metabolism and translation (Wang Z. et al, 2016). Nevertheless, the mechanism of the shifts of the two conidiation patterns remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…They are the infective form of entomopathogenic fungi, essential for their pathogenicity (Schrank and Vainstein, 2010). In filamentous fungi, normal conidiation and microcycle conidiation are the two patterns of asexual conidiation (Zhang et al, 2010; Jung et al, 2014; Wang Z. et al, 2016). In normal conidiation, asexual conidia are produced at the top or sides of the hyphae in a subsequent budding-like process for proper vegetative growth, whereas microcycle conidiation occurs when fungi are subjected to unfavorable environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal conidiation, conidia are generated after the mycelia have properly extended, while in microcycle conidiation, new conidia can be formed directly from the germinated ones ( 8 ). Under certain, specific conditions, the two patterns are interconvertible ( 9 11 ). Two conidiation patterns also exist in Metarhizium acridum , a locust-specific pathogen, and microcycle conidiation exhibited great potential for improving the productivity and quality of conidia ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fungi can bypass the mycelia period in MC and develop secondary conidia from germ tubes or directly from conidial cells [ 1 , 4 , 14 ]. MC is a special survival mechanism of fungi under adverse conditions, such as high temperature [ 10 , 11 , 15 ], extreme pH [ 16 ], high salt content [ 17 ], and nutritional deficiencies [ 4 , 18 , 19 , 20 ]. Among them, nutritional deficiency is the important factor that affects the fungal growth and development.…”
Section: Introductionmentioning
confidence: 99%